THE ANALYSIS OF COMMUNICATION STRATEGIES USED BY STUDENTS FROM MIXED MARRIAGE FAMILIES IN ATTENDING THE TEACHING AND LEARNING PROCESS IN BUSINESS HOSPITALITY DEPARTMENT OF BALI TOURISM INSTITUTE NUSA DUA - ., NI LUH SUPARTINI; ., PROF. DR. I KETUT SEKEN, M.A.; ., DRS. I WAYAN SUARNAJAYA, M.A., P.hD (Jurnal Pendidikan Bahasa Inggris, 2015)
Penelitan ini bertujuan untuk menginvestigasi strategi komunikasi yang digunakan oleh siswa local dan siswa blasteran (campuran) dari Jurusan Bisnis Perhotelan di Sekolah Tinggi Pariwisata Nusa Dua Bali. Masalah yang diteliti diformulasikan ke dalam: 1) jenis-jenis strategi komunikasi siswa, 2) alasan menggunakan strategi tertentu, 3) perbandingan antara strategi komunikasi yang digunakan siswa lokal dan siswa blasteran, 4) persepsi guru terhadap strategi komunikasi yang digunakan siswa. Subjek penelitian ini adalah dua siswa blasteran dan siswa-siswa lokal di kelas Bisnis Perhotelan semester dua. Penelitian ini dirancang dengan menggunakan kualitatif deskripsi serta instrumen yang digunakan adalah instrumen manusia, rekaman proses belajar- mengajar di kelas dan wawancara. Hasil yang dtemukan adalah terdapat sebelas strategi yang digunakan oleh siswa lokal dan siswa blasteran selama proses belajar mengajar. Siswa blasteran lebih suka menggunakan strategi menjelaskan kata, strategi meninggalkan pesan dan strategi pengulangan. Untuk siswa lokal, mereka cenderung menggunakan strategi menerjemahkan kata per kata dan strategi alih bahasa. Berdasarkan hasil yang dtemukan, siswa menggunakan strategi tertentu bertujuan untuk memfasilitasi percakapan mereka agar mencapai tujuan komunikasi dalam proses belajar mengajar. Pandangan guru terhadap strategi yang digunakan siswa adalah pemilihan strategi yang dgunakan siswa dipengaruhi oleh bahasa pertama mereka dan kemampuan mereka dalam Bahasa Inggris.Kata Kunci : strategi komunikasi, siswa blasteran (campuran), siswa local, dan pandangan guru This study aimed to investigate the Communication Strategies (CS) used by local and mixed marriage students of Business Hospitality Department of Bali Tourism Institute Nusa Dua Bali. The problems were formulated into four major points: 1) types of communication strategies (CS) used by local and mixed marriage students, 2) reasons for the use of certain CS, 3) the comparison of CS used by local and mixed marriage students and 4) teacherâs perception towards CS used by the students. The subjects were two mixed marriage students and local students of Business Hospitality class in second sesmster. This recent study was designed with descriptive qualitative and the instruments being used were human instrument, recording of teaching and learning process and interview. There were eleven (11) types of communication strategies (CS) found in teaching and learning process used by mixed marriage and local students. Mixed marriage students preferred to use circumlocution strategy, message abandonment and repetition. For local students, they frequently used literal translation and language switch. Based on the findings, they used certain strategies to facilitate their conversation in order to get the goal of communication during teaching and learning process. The teacherâs perception towards strategies used by the students was the choice of CS which was influenced by their first language and their proficiency in English.keyword : Communication Strategies, Mixed Marriage Students, Local Students, and Teacherâs Perception